Physics Multimedia Development Using Camtasia Studio 8 Software Vector Material - Zulhen, Ahmad; Giarti, Giarti (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2015)
Media in the teaching and learning process tends to be defined as graphic, photographic or electronic tools for capturing, processing and reconstructing visual or verbal information. This research aims to (1) develop physics learning videos using Camtasia studio8 vector material software for class X Senior high school. This research is motivated by the development of Information and Communication Technology (ICT) in the world of education to assist the teaching and learning process. One of the uses of ICT is the development of learning videos using Camtasia studio8 software. The steps in this research and development using the ADDIE model include: (1) Analysis, (2) Design, (3) and Development. But the implementation stage was not carried out because it was only a product trial. Learning video materials as physics learning media that have been completed are then validated by a team of media experts and a team of material experts. The result of this development is in the form of vector material physics learning video media. This media was declared suitable for use after being validated twice by media expert validators and material experts.